2014
DOI: 10.1037/a0035318
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral economic approach to assessing demand for marijuana.

Abstract: In the U.S., marijuana is the most commonly used illicit drug. Its prevalence is growing, particularly among young adults. Behavioral economic indices of the relative reinforcing efficacy (RRE) of substances have been used to examine the appeal of licit (e.g., alcohol) and illicit (e.g., heroin) drugs. The present study is the first to use an experimental, simulated purchasing task to examine the RRE of marijuana. Young-adult (M age = 21.64 years) recreational marijuana users (N = 59) completed a computerized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 64 publications
9
111
1
Order By: Relevance
“…MPT data were consistent with previous research employing purchase tasks to assess drug demand (e.g., Collins et al, 2014; MacKillop et al, 2008; Murphy and MacKillop, 2006), as estimated consumption of marijuana hits decreased as price per hit increased. Moreover, the MPT demonstrated robust convergent validity, as demand metrics (i.e., intensity, O max , and elasticity) were significantly associated with marijuana use variables (i.e., subjective marijuana craving, age at initiation of regular marijuana use, marijuana dependence symptoms, and percent of marijuana use days).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…MPT data were consistent with previous research employing purchase tasks to assess drug demand (e.g., Collins et al, 2014; MacKillop et al, 2008; Murphy and MacKillop, 2006), as estimated consumption of marijuana hits decreased as price per hit increased. Moreover, the MPT demonstrated robust convergent validity, as demand metrics (i.e., intensity, O max , and elasticity) were significantly associated with marijuana use variables (i.e., subjective marijuana craving, age at initiation of regular marijuana use, marijuana dependence symptoms, and percent of marijuana use days).…”
Section: Discussionsupporting
confidence: 85%
“…The first study examining the behavioral economics of marijuana utilized a novel marijuana purchase task (MPT) to investigate simulated demand for marijuana (Collins et al, 2014). Collins and colleagues (2014) administered a MPT to 59 recreational marijuana users, asking them to estimate the number of marijuana joints they would purchase at increasing prices. The study employed ecological momentary assessment to collect real-time marijuana use data and subsequently investigated the associations between marijuana use and MPT demand indices.…”
Section: Introductionmentioning
confidence: 99%
“…Further, although our results suggesting that alcohol demand is relevant to marijuana use outcomes is interesting, future research should include a measure of marijuana demand (Collins, Vincent, Yu, Liu, & Epstein, 2014). Finally, although research has shown that college student self-report measures of substance use are generally accurate (Hagman, Clifford, Noel, Davis, & Cramond, 2007), a biological measure of alcohol or marijuana use may have been helpful in confirming these results.…”
Section: Implications and Future Directionsmentioning
confidence: 65%
“…Future studies should extend these findings to other addictive commodities, such as comparing preferences for hypothetical and actual cigarettes (Jacobs and Bickel 1999; MacKillop et al 2008) or illicit drugs (Collins et al 2014). More broadly, this study offers additional support for utilizing purchase tasks as efficient and valid assessments of behavioral economic demand.…”
Section: Discussionmentioning
confidence: 93%
“…Demand can be readily assessed via self-report purchase tasks that ask individuals how much of an addictive commodity (e.g., alcohol, tobacco, illicit drugs) they would consume at escalating prices (Collins et al 2014; Jacobs and Bickel 1999; MacKillop et al 2008; Murphy and MacKillop 2006). Studies using alcohol purchase tasks (APTs), for instance, have found that alcohol demand is associated with quantity/frequency of alcohol consumption, alcohol use disorder severity, and treatment outcomes (e.g., Murphy and MacKillop 2006; MacKillop, Miranda, et al 2010; MacKillop and Murphy 2007).…”
Section: Introductionmentioning
confidence: 99%